Substrate‐induced dimerization of elaiophylin glycosyltransferase reveals a novel self‐activating form of glycosyltransferase for symmetric glycosylation. Issue 10 (27th September 2022) - Xu, Tingting; Gan, Qingqing; Liu, Qiang; Chen, Ruidong; Zhen, Xuhui; Zhang, Changsheng; Liu, Jinsong
Abstract : The structure of the elaiophylin glycosyltransferase homodimer reveals a novel model of a self‐activating form of a member of glycosyltransferase family 1 that binds the symmetric substrate. Abstract : Elaiophylin (Ela), a unique 16‐membered symmetric macrodiolide antibiotic, displays broad biological activity. Two rare 2‐deoxy‐l ‐fucose moieties at the ends of Ela are critical for its activity. Previously, elaiophylin glycosyltransferase (ElaGT) was identified as the enzyme that is responsible for the symmetric glycosylation of Ela, acting as a potential enzymatic tool for enhancing the diversity and activity of Ela. However, a symmetric catalytic mechanism has never been reported for a glycosyltransferase (GT). To explore the catalytic mechanism, the structure of ElaGT was determined in four forms: the apo form and Ela‐bound, thymidine diphosphate‐bound and uridine diphosphate‐bound forms. In the Ela‐bound structure, two ElaGTs form a `face‐to‐face' C 2‐symmetric homodimer with a continuous acceptor‐binding pocket, allowing a molecule of Ela to shuffle through. Interestingly, this dimer interface resembles that of the activator‐dependent GT EryCIII with its activator EryCII. Sequence analysis also indicates that ElaGT belongs to the activator‐dependent GT family, but no putative activator has been identified in the Ela gene cluster. It was then found that the ElaGT homodimer may utilize this `face‐to‐face' arrangement to stabilize the Ela‐binding loops on the interface and to simultaneously allosterically regulate the catalytic center. Therefore, these structures present a novel self‐activating model for symmetric sugar transfer in the GT family and a new potential regulation site for substrate specificity.